2022
DOI: 10.1097/aln.0000000000004302
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Citation of Retracted Articles in Anesthesiology and Intensive Care Medicine Publications

Abstract: Background Retracted articles represent research withdrawn from the existing body of literature after publication. Research articles may be retracted for several reasons ranging from honest errors to intentional misconduct. They should not be used as reliable sources, and it is unclear why they are cited occasionally by other articles. This study hypothesized that several mechanisms may contribute to citing retracted literature and aimed to analyze the characteristics of articles citing retra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…These models do not consider that prominent sources (such as journals or search engines) can potentially spread the correction to large portions of the population at once. However, missing or unclear labeling of articles as ‘retracted’ on both journals and search engines can also contribute to the citation of the manuscripts 3. In addition, it has been shown that several publishers do not transmit to PubMed the metadata regarding retraction notices in a correct or timely fashion 13…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These models do not consider that prominent sources (such as journals or search engines) can potentially spread the correction to large portions of the population at once. However, missing or unclear labeling of articles as ‘retracted’ on both journals and search engines can also contribute to the citation of the manuscripts 3. In addition, it has been shown that several publishers do not transmit to PubMed the metadata regarding retraction notices in a correct or timely fashion 13…”
Section: Discussionmentioning
confidence: 99%
“…Data suggest that one out of four researchers does not check references before submission, with almost half failing to adopt a strategy to prevent the citation of retracted literature in their manuscript 3. Moreover, compiling an accurate reference list may be a monotonous and repetitive task increasing the risk of errors due to inattentional blindness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And just as citing overturned precedents can lead to bad legal outcomes, citing retracted papers can lead to a deeply flawed base of evidence for clinical decision-making. In this issue, a study by De Cassai et al 1 demonstrates that anesthesiology is not immune to the citation of retracted papers.…”
Section: How To Stop the Unknowing Citation Of Retracted Papersmentioning
confidence: 99%